The Experimentation of Contextual and Realistic Learning Models in terms of Interpersonal Intelligence - Susiaty, Utin Desy; Hodiyanto, Hodiyanto (Universitas PGRI Madiun, 2019)
The aims of this study is to find out: (1) a better learning model between contextual, realistic or conventional; (2) better learning outcomes between students with high, medium or low interpersonal intelligence; (3) better learning outcomes between students with high, medium or low interpersonal intelligence on each learning model; (4) a better learning model between contextual, realistic or conventional at each level of interpersonal intelligence. This research is using the experimental method. The sampling technique is cluster random sampling. Data collection tools used were questionnaires and tests. The data analysis technique used is the analysis of three-way variance with unequal cells. The results showed that: (1) contextual learning models are better than realistic but provide the same learning outcomes as conventional, while realistic and conventional learning outcomes are equally good; (2) students who have high, medium or low interpersonal intelligence have the same learning outcomes; (3) In each learning model, students with high, medium and low interpersonal intelligence have the same learning outcomes; (4) At each level of interpersonal intelligence, the contextual learning model is better than realistic and conventional.